Assessment of carotenoid and tocopherol level in sweet corn inbred lines during kernel development stages - Feng, Faqiang; Wang, Qingfeng; Zhang, Jing; Yang, Ruichun; Li, Xiaoqin (The Indian Journal of Genetics and Plant Breeding, 2016)
Among cereals, only maize has amply amount of carotenoids and tocopherols.This study investigated the carotenoids and tocopherols accumulation of the kernels at the 15, 18, 21, 24, 27 and 30 days after pollination using 10 sweet corn inbred lines. The results showed that the contents of carotenoid components from high to low were zeaxanthin, lutein, â-cryptoxanthin, â-carotene and á-carotene.There were no significant differences between 18 and 21days among 5 carotenoid components. The contents of tocopherol components from high to low were ã -tocopherol, á-tocopherol and ä-tocopherol. There were no significant differences between 21, 27 and 30 days among 3 tocopherol components. The variance components of genotypes were higher than that of days after pollination. The content of both carotenoid and tocopherol components reached the peak at 21 and hence, this time was regarded as the optimal harvest period.